Analisis Laju Emisi Gas Buang Karbon Monoksida (Qco) Pada Udara Ambient di Jalan Lintas Mendalo Darat Kabupaten Muaro Jambi - Herawati, Peppy; Riyanti, Anggrika; Adriansyah, Endi; Prasasti, Dinda; Suzana, Asih (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Carbon monoxide (CO) is a compound that has no smell, taste or color. The compound carbon monoxide (CO) originates from vehicle exhaust emissions from incomplete engine combustion, when exposed it will have an impact on disrupting the path of oxygen binding to hemoglobin in the blood. The Mendalo Darat road is one of the busiest roads in Jambi Province, so it is prone to traffic jams due ti the dense mobilization of motorized vehicles. This can result in a decrease in ambient air quality due to the concentration of carbon monoxide (CO) compounds. This study aims to determine the quality of ambient air in the parameters of carbon monoxide (CO) on the Mendalo Darat highway and the resulting emission rate. Based on the research results for 3 days, namely Sunday (Weekend), Monday, and Tuesday (Weekday), it shows that the highest density is on Tuesday morning which is 17,994 units. Meanwhile, the lowest vehicle volume was on Sunday afternoon point III with a vehicle volume of 6.576 units. The results showed that the highest carbon monoxide (Qco) emission rate on Sunday was at point I in the afternoon of 97.114 µg/m.s, at point II in the afternoon that was 52.665 µg/m.s, and point III in the afternoon wa 52.644 µg/m.s. on Monday, the highest emission rate of carbon monoxide (Qco) was at point I in the afternoon of 106.830 µg/m.s. followed by point II in the afternoon, which was 86.795 µg/m.s on Tuesday, and point III, which was 86.749 µg/m.s. on Tuesday, point I with the largest carbon monoxide (Qco) emission rate was 114.290 tn the morning, followed by point I, which was 109.601 in the afternoon